(untitled) (Geologica Macedonica, 2023)
The paper presents information about our latest study of radon and radium in drinking water from the public water fountains situated in central parts of the Kratovo-Zletovo volcanic area. Results for the radon in water measurements were as follows: Fountain 1 to Fountain 4 samples, ranged from 6.63 up to 157.73 Bq L-1. Obtained results for the radium in water, Fountain 1 to Fountain 4 samples, ranged from 0.20 up to 1.08 Bq L-1. Both, radon and radium measurements, in water samples from certain fountains have shown significantly higher values than the strictest standards given by the United States Environmental Protection Agency (USEPA) and World Health Organization (WHO), respectively. The committed effective doses for the population consuming the water directly from the fountains or as self-bottled waters from the Kratovo-Zletovo volcanic area were estimated using the concentration of 222Rn and 226Ra in water samples, ranged from 45.47 mSv y-1 to 709.36 mSv y-1, which once again for some fountains were higher than the WHO recommended values of max. 100 mSv y-1.